Pengembangan Desain UI/UX Fitur Baru Pada Aplikasi StuntShield Menggunakan metode User-Cantered Design - M Miskun Arrihussalam; Ridwan Setiawan (Jurnal Algoritma, 2026)
This study aims to redesign the StuntShield application interface using a User-Centered Design (UCD) approach. This application aims to support stunting prevention by providing nutritional information and interactive features for parents, integrated health service posts, and community health centers. The development process was carried out in four UCD stages, namely identifying the context of use, formulating user needs, creating design solutions, and evaluating prototypes. Data collection was conducted through interviews with developers and the distribution of questionnaires to potential users. The design was created using Figma and focused on three user roles. The evaluation was conducted using the System Usability Scale (SUS) involving 21 respondents. The test results showed an average score of 73.63, which falls into the “Good” category, indicating that the interface design was well received by users. This study contributes to the development of UI/UX based on the real needs of users for digital health service applications.